Chhana binders effects on the quality of Rosogolla - Begum, J; Islam, MN; Rashid, MH; Begum, S; Islam, MZ; Shekh , AL; Siddiki, MSR (Bangladesh Journal of Animal Science, 2022)
A study was carried out to investigate the effect of different levels of Chhana binder on the sensory and chemical quality of Rosogolla. Therefore, two (02) types of Chhana binders in different percentage such as 3, 5 and 7% wheat flour as well as 3, 5 and 7% rice flour (w/w) were used to prepare Rosogolla to find out a suitable Chhana binder for manufacturing good quality Rosogolla. Based on sensory evaluation, the highest score was obtained from 5% wheat flour and lowest score was from 5% rice flour, might be due to wheat flour contain gluten. From chemical analysis, the protein and carbohydrate content among the samples differed significantly (p< 0.01) and the highest values were noted for 7% wheat flour and rice flour, respectively. The highest and least mean values of moisture content were recorded for Rosogolla obtained from 3% wheat flour and 7% rice flour, respectively. Among different Chhana binder, 5% wheat flour was found best suitable for quality Rosogolla making. Bangladesh Journal of Animal Science. 51(1):12-16